THE CLINICAL AND PATHOGENETIC FEATURES OF OSTEOARTHROSIS IN WOMEN WITH DIFFERENT TYPES OF OBESITY - Darya Andreyevna Kopylova; V A Ostapenko (Научно-практическая ревматология, 2012)
Objective: to study the pattern of impact of abdominal obesity on the clinical manifestations of osteoarthrosis (OA) in women. Subjects and methods. Forty-three patients aged 48 to 73 years, who had been diagnosed as having osteoarthrosis in accordance with the American College of Rheumatology criteria, were examined. Anthropometric characteristics, the duration of the disease, the degree of functional failure, and the levels of adipocytokines (adiponectin, interleukins (IL)-4 and -6) were estimated and X-ray study of the joints conducted. The nature of effects of adipokines on the course of OA and the degree of arthralgies were determined. Results and discussion. In abdominal obesity, the level of adiponectin and anti-inflammatory IL-4 was lower and that of proinflammatory IL-6 was higher than those in femoral-gluteal obesity. The elevated IL-6 level was associated with severer X-ray changes, more functional failure, and more obvious joint pains. At the same time, IL-4 and adiponectin levels were decreased in severe OA. Thus, abdominal obesity is accompanied by the change in the secretion of IL-6, IL-4, and adiponectin, which are in turn associated with the unfavorable course of OA in women.